Answer:
(a) (x+1)(x-1)
(b)(3x+1)(3x-1)
(c) (x+3)(x+5)
(d)(2x+5)(2x+3)
(e)(x+y)(x-y)
(f)
Explanation:
We have to factorize the following expressions:
(a) x²-1 =(x+1)(x-1) (Answer) {Since we know the formula (a²-b²) =(a+b)(a-b)}
(b) 9x²-1 =(3x+1)(3x-1) (Answer) {Since we know the formula (a²-b²) =(a+b)(a-b)}
(c) x²+8x+15 = x² +3x+5x+15 =(x+3)(x+5) (Answer)
(d) 4x²+16x+15 =4x²+10x+6x+15 = 2x(2x+5) +3(2x+5) =(2x+5)(2x+3) (Answer)
(e) x²-y² =(x+y)(x-y) (Answer)
(f)
(Answer) {Since we know the formula (a²-b²) =(a+b)(a-b)}